Hubungan durasi operasi dengan kejadian prolonged mechanical ventilation pada pasien post operasi CABG di ruang ICU - Fania Putri Alya; Ria Indriani; Regina Indah Kumalasari; Firman Sugiharto; Diki Ardiyansyah; Heni Aguspita Dewi; Rahayu Setyowati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Prolonged mechanical ventilation (PMV) is a complication after coronary artery bypass graft (CABG) surgery that increases morbidity, mortality, and length of stay in the ICU. Surgical duration is often considered a factor influencing the incidence of PMV, but previous studies have shown inconsistencies. Purpose: To analyze the relationship between surgical duration and PMV incidence in post-CABG patients in the ICU. Method: This study used a retrospective cohort design with a quantitative approach. The study sample consisted of 237 medical records of post-CABG patients in the ICU of Dr. Hasan Sadikin General Hospital, Bandung. The sample was selected using consecutive sampling techniques according to inclusion and exclusion criteria. Data were collected using a checklist developed by the researchers. Data were analyzed univariately and bivariately using Pearson's correlation test. Results: The mean duration of mechanical ventilation in patients with PMV was 1619.66 ± 836.38 minutes (±27 hours), with a range of 730–3850 minutes. The average surgical duration was 252.52 ± 47.22 minutes. The analysis showed no significant association between surgical duration and the incidence of PMV (r = 0.059; p = 0.367). Conclusion: Surgical duration was not significantly associated with the incidence of PMV in post-CABG patients. This indicates that PMV is a multifactorial condition influenced not only by surgical duration but also by other clinical and perioperative factors. Therefore, a comprehensive clinical approach is needed to prevent and manage PMV. Suggestion: ICU nurses need to conduct more comprehensive monitoring of post-CABG patients, taking into account other clinical factors that may influence the ventilator weaning process. Furthermore, the development of integrated clinical protocols for mechanical ventilation management is needed to support accelerated patient recovery. Future research is recommended to explore other factors contributing to PMV with a more robust design to produce a more comprehensive and applicable predictor model in clinical practice. Keywords: Complication After Coronary Artery Bypass Graft (CABG); Intensive Care Unit; Mechanical Ventilation; Prolonged Mechanical Ventilation; Surgical Duration.